Penerapan Metode Lean UX Untuk Sistem Poin dan Loyalty Custumer Pada Website Pemesanan Makanan Kitchen - Yusuf, Imam Fiqri Haikhal; Yulindawati, Yulindawati; Haristyawan, Ivan (Journal of Informatics, Electrical and Electronics Engineering, 2025)
The Lean UX method is a design approach that emphasizes collaboration, rapid experimentation, and continuous validation to produce products that meet user needs. On the Kitchen food ordering website, Lean UX was applied to design and develop a points system and customer loyalty system to increase user engagement and retention. The points system was chosen because initial findings from user research indicated that customers wanted clear and sustainable incentives to continue ordering through the Kitchen platform. The Lean UX process began with formulating a hypothesis regarding the benefits of the points system, then continued with the creation of an MVP (Minimum Viable Product) in the form of a reward feature prototype. The prototype was iteratively tested with users through a Build Measure Learn cycle to obtain rapid feedback and identify pain points in the user experience. Through this series of experiments, the team was able to adjust the interface, interaction flow, and reward structure based on real data from user behavior. The results of implementing the Lean UX method showed that iterative testing helped accelerate the feature validation process, reduce development risks, and increase the relevance of the points system to user needs. Thus, Lean UX proved effective in creating loyalty features that not only improve the user experience, but also support Kitchen's business goals of retaining customers and increasing order frequency. to design and develop a points system and customer loyalty as an effort to increase user engagement and retention. The points system was chosen because initial findings from user research showed that customers wanted clear and sustainable incentives to continue ordering through the Kitchen platform. The Lean UX process began with the formulation of a hypothesis regarding the benefits of the points system, then continued with the creation of an MVP (Minimum Viable Product) in the form of a reward feature prototype. The prototype was tested with users iteratively through the Build–Measure–Learn cycle to obtain rapid feedback and identify pain points in the user experience. Through this series of experiments, the team was able to adjust the interface, interaction flow, and reward structure based on real data from user behavior. The results of implementing Lean UX methods showed that iterative testing helped accelerate the feature validation process, reduce development risk, and increase the relevance of the points system to user needs. Thus, Lean UX proved effective in creating a loyalty feature that not only improved the user experience but also supported Kitchen's business goals of retaining customers and increasing order frequency.